Biologically inactive growth hormone caused by an amino acid substitution. - Takahashi, Y (1997)
Short stature caused by biologically inactive growth hormone (GH) is characterized by lack of GH action despite high immunoassayable GH levels in serum and marked catch-up growth to exogenous GH administration. We found a heterozygous single-base substitution (A-->G) in exon 4 of the GH-1 gene of a girl with short stature, clinically suspected to indicate the presence of bioinactive GH and resulting in the substitution of glycine for aspartic acid at codon 112. We confirmed the presence of mutant GH in the serum using isoelectric focusing analysis. The locus of mutation D112G was found within site 2 of the GH molecule in binding with GH receptor (GHR)/GH binding protein (GHBP). The expressed recombinant mutant GH tended to form a 1:1 instead of the 1:2 GH-GHBP complex normally produced by wild-type GH. The formation of a 1:2 GH-GHBP complex is compatible with the dimerization of GHRs by GH, a crucial step in GH signal transduction. Mutant GH was less potent than wild-type GH not only in phosphorylation of tyrosine residues in GHR, janus kinase 2 (JAK2), and signal transducers and activators of transcription 5 (STAT5) in IM-9 cells, but also in metabolic responses of BaF/GM cells, a stable clone transfected with cDNA of the chimera of the extracellular domain of human GHR, the transmembrane and the cytoplasmic domain of the human thrombopoietin receptor. These results indicate that the D112G mutation in the GH-1 gene causes production of bioinactive GH, which prevents dimerization of GHR and is therefore responsible for the patient's short stature.